Characterization of aquatic organic matter: Assessment, perspectives and research priorities. (15th October 2019) - Derrien, Morgane; Brogi, Simona Retelletti; Gonçalves-Araujo, Rafael
Abstract: Organic matter (OM) refers to the largest reactive reservoir of carbon-based compounds on Earth. Aside of its role as a source of carbon, OM is also actively involved in a wide range of ecological functions. It also plays an important role in the solubility, toxicity, bioavailability, mobility and distribution of pollutants. Therefore, OM is a key component in the local and global carbon cycle. About 12, 000 articles containing organic matter in the title were published during the past decade, with a continuous increasing number each year (ISI Web of Science). Although this topic was widely explored and its interest has significantly increased, some limitations remain. These limitations can be technical (e.g., pre-treatment processes, low-resolution instrument, data handling) and can be related to the current approach. In this review, we first present the current strategies and tools to characterize the organic matter in the aquatic environment, then we tackle several aspects of current characterization limitations. Finally, we suggest new perspectives and priorities of research to improve the current limitations. From our point of view, simultaneous studies of particulate and dissolved OM fractions should be prioritized and multi-disciplinary approach, creation of databases, controlled experiments and collaborative works should be the next targets for future OM research priorities. Graphical abstract: Image 1 Highlights: Current strategies to characterize organic matter are evaluated. Several aspects of the current characterization limitations are tackled. New perspectives and priorities of research are suggested. Simultaneous studies of particulate and dissolved organic matter should be prioritized. Holistic approaches should be the turning point of the current approach.